Pengaruh Media Sosial Terhadap Persepsi Diri dan Pembentukan Identitas Remaja di Indonesia - Egi Regita; Nabilah Luthfiyyah; Nur Riswandy Marsuki (Institut Nalanda, 2024)
This research aims to see the influence of social media on teenagers in Indonesia. Teenagers are trapped in digital social life due to excessive use of social media in living a variety of lifestyles. The presence of social media changes the private environment into a public environment. Teenagers do everything on social media to determine and shape their self-identity. Therefore, this article discusses the influence of social media in the formation of adolescent identity. The research method used is a qualitative research method, more precisely library research. Specific characteristics that are used as a basis for developing research knowledge include; This research is confronted directly with the data or text presented, not with field data or through eyewitnesses in the form of events, researchers only deal directly with sources that already exist in the library or ready-to-use data, as well as secondary data used. The research results found that social media influences one's self-perception and identity formation is a complex phenomenon that has both positive and negative effects. Social media can be a powerful tool for communicating and building identity, but it can also lead to mental health problems, negative comparisons, and social stress. How people see themselves can be influenced by edited content, balloon filters, and pressure to conform to standards. Conversely, social media can facilitate social support, positive interactions, and the exchange of ideas that can increase a person's self-confidence. Individuals should understand the possible impact, maintain balance in social media use, and select content carefully